From Information Seeking to Social Support: Utilities of WhatsApp Group for Health Education and Postpartum Healing among CS Mothers in Nigeria - Umar Olansile Ajetunmobi (International Journal of Qualitative Research, 2022)
Previous studies on computer-mediated communication have investigated the use of WhatsApp groups for health education, health communication, and behavior change, but no empirical study had documented the experiences of Cesarean Section (CS) mothers on their use of WhatsApp groups for health education, information seeking and postpartum healing. This study identifies the post-CS goals of mothers who joined Csection Mum Community WhatsApp group, examines the extent to which the group’s activities satisfied those goals, investigates why they felt safe disclosing their personal health information in the group and explores the role of interpersonal empathic communication on their postpartum healing. Using Online Focus Group Discussion (OFGD) to collect data from twenty-seven CS mothers, and guided by some propositions of uses and gratifications, social penetration theories, and empathic model, the findings revealed that the WhatsApp group satisfied the mothers’ informational, educational, experiential learning and social support needs. Their affinity with the group’s activities influenced their spontaneous self-disclosure in the group. It was also found that interpersonal empathic communication improved the postpartum depression healing process of the mothers. It, therefore, recommends that hospitals (that operate on patients) empower adult mental health nurses or clinical psychiatrists to engage CS mothers and their caregivers (family members, spouses, etc.) in psycho-education, especially empathic communication, before discharging the mothers.